OPTIMALISASI PROGRAM TAHFIDZ QUR’AN DALAM MENINGKATKAN KUALITAS HAFALAN DI MI MIFTAHUL JANNAH DUDUKSAMPEYAN GRESIK - Firdha Masya Aulia Syafitri; Mukhlishah AM; Ni’matus Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the optimization of the tahfidzul Qur’an program in improving students’ memorization quality at MI Miftahul Jannah Duduksampeyan Gresik. The study emphasizes the importance of learning the Qur’an from an early age as an effort to shape a Qur’anic generation, although challenges remain, such as limited fluency in reading among some students. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation involving the principal, tahfidz teachers, and students. The findings indicate that the tahfidz program plays a significant role in fostering students’ religiosity, discipline, and memorization skills, with tahfidz teachers serving as guides, motivators, role models, and evaluators. Supporting factors include interest, talent, intelligence, and motivation, while inhibiting factors consist of weak mastery of makharijul huruf, lack of patience, and low commitment in memorization. This research contributes theoretically to the development of Islamic education management and provides empirical insights into the implementation of the tahfidzul Qur’an program in Islamic elementary schools.